State of stocks of pacific salmons in the basin of Avacha Bay (southeastern Kamchatka) in 1985–2019 - G. V. Zaporozhets; O. M. Zaporozhets (Известия ТИНРО, 2020)
State of pacific salmon stocks is considered for the basins of the Avacha and Paratunka Rivers in 1985–2019. Significant decline of the stocks is noted that is associated with anthropogenic impact growth. Total number of producers for five salmon species in the Paratunka is almost twice higher than in the Avacha, with the largest portion of pink salmon, then chum salmon, lower portion of coho salmon, and the smallest portions of sockeye and chinook salmons, which need special protection. The main biological parameters of salmons are analyzed for both rivers, as body length, weight, fecundity, sex ratio and age structure, by species. Relationships between the parameters are revealed; their long-term trends are determined. Abundance of wildly and artificially hatched chum salmon is compared.